Microsurgical tissue autotransplantation in the treatment of open limb fractures - E. Yu. Shibayev; P. A. Ivanov; D. A. Kisel (Трансплантология (Москва))
Background. There is now only one method for replacement of virtually any integumentary defects differing in extent, which satisfies all the requirements of primary plastic repair – microsurgical autotransplantation of tissue units on a vascular pedicle. Primary plastic repair by microsurgical autotransplantation makes it possible not only to perform adequate reconstructive manipulations of an injured limb, but also to create the optimal conditions for delayed surgical interventions.Materials and methods. Since 2000, the N.V. Sklifosovsky Research Institute of Emergency Care has been performing autotransplantation of vascularized tissue units to cover soft tissue defects. For this time, 57 flaps have been grafted in 57 patients with open limb bone fractures. For closure of soft tissue defects, the authors have successfully applied free autografts comprising the muscles and skin.Results and discussion. Out of the 57 primary microsurgical autotransplantations of tissue flaps, only 4 cases required emergency intervention; the others needed delayed one. To close soft tissue defects, the authors successfully applied free autografts comprising the muscles and skin. All the transplanted autografts got implanted completely.Conclusion. The used procedure furnishes a means of minimizing donor site damage and ultimately improves both functional and aesthetic surgical results. The authors’ experience permits one to recommend a more active introduction of microsurgical plastic methods into clinical practice.